2010
DOI: 10.1007/s00296-010-1693-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of metabolic syndrome in patients with chronic low back pain

Abstract: The aim of our study was to investigate the frequency of the metabolic syndrome in chronic low back pain and evaluate the differences in clinical and functional parameters in chronic low back pain patients with and without metabolic syndrome. Patients complaining of low back pain complaint lasting for at least 2 months were included in the study. In order to establish functional deficiency, Roland-Morris Disability Questionnaire, Istanbul Low Back Pain Disability Index and Oswestry Disability Index were used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
2
13
1
1
Order By: Relevance
“…The high prevalence of metabolic syndrome, the mean age and female predominance in our series were observed in other African works [7] According to Duroz, et al, high body mass index, chronic low back pain, old age was associated with bad evolution of back pain [8]. For Ono, association was significantly in women and there was no association between low back pain and metabolic syndrome in men [9].…”
Section: Discussionsupporting
confidence: 55%
“…The high prevalence of metabolic syndrome, the mean age and female predominance in our series were observed in other African works [7] According to Duroz, et al, high body mass index, chronic low back pain, old age was associated with bad evolution of back pain [8]. For Ono, association was significantly in women and there was no association between low back pain and metabolic syndrome in men [9].…”
Section: Discussionsupporting
confidence: 55%
“…A recent systematic review identified a relationship between MetS and Achilles tendinopathy 30. Furthermore, MetS is more prevalent in people with neck pain,31 low back pain32 33 and knee osteoarthritis 34. One study showed that MetS was not associated with adhesive capsulitis, although associations with type II DM and hypertension were identified 35…”
Section: Introductionmentioning
confidence: 99%
“…Findings from population-based and clinic studies indicate that presence of chronic low back pain is related to an elevated incidence of metabolic syndrome (Duruoz, Turan, Gurgan & Deveci, 2013; Ha, 2011). High BMI, and in particular greater waist circumference, are also associated with chronic pain (Hitt, McMillen, Thorton-Neaves, Koch & Cosby, 2007; Goodson et al, 2013; Ray, Lipton, Zimmerman, Katz, Derby, 2011; Stone & Broderick, 2012; Urquhart et al, 2011; Wright et al, 2010).…”
mentioning
confidence: 99%